Understanding Online Purchase Decisions : The Role of the Bandwagon Effect, Lifestyle, and Digital Payments - Awalul Khairi; Zainal A Haris; Rina Mariana; Dimas Perdana Oskar (Brilliant International Journal Of Management And Tourism, 2025)
This study investigates the determinants of online purchase decisions by examining the influence of the bandwagon effect, lifestyle, and digital payment usage among urban consumers aged 18–40 in Padang City, Indonesia. Using a quantitative approach, data were collected from 170 respondents through a structured questionnaire and analyzed with multiple linear regression. Descriptive analysis revealed high average scores for all variables, indicating a generally positive perception among respondents. Regression results showed that the three variables jointly explain 73.7% of the variance in online purchasing behavior. Furthermore, all three predictors—bandwagon effect, lifestyle, and digital payments—exerted significant partial effects, with digital payment being the strongest contributor. The bandwagon effect emerged as a powerful social driver, suggesting that peer influence and perceived popularity of products significantly encourage individuals to engage in similar purchasing patterns. Lifestyle, reflecting personal values, interests, and routines, was also found to meaningfully affect consumer choices, highlighting that purchasing decisions are often aligned with self-identity and aspirational living standards. Digital payment usage demonstrated the most substantial impact, emphasizing the importance of transaction speed, ease, and security in fostering online shopping adoption. These findings indicate that modern online consumer behavior is not solely the result of individual preferences but is shaped by a complex interplay of social influence, lifestyle aspirations, and technological convenience. The results hold practical implications for e-commerce platforms, which can leverage social proof strategies, lifestyle-oriented marketing content, and seamless payment integrations to enhance consumer engagement and conversion rates. Marketers are encouraged to design campaigns that blend social validation cues, targeted lifestyle messaging, and promotions tied to preferred payment methods to maximize market penetration. This study contributes to the growing literature on digital commerce by illustrating how psychological, sociocultural, and technological factors converge to influence purchasing intentions in emerging markets